Peran Orang Tua dalam Membina Akhlak bagi Anak dalam Lingkungan Keluarga di Jorong Balai Panjang Nagari Saniang Baka - Muhammad Rusdi; Muhiddinur Kamal; Salmi Wati; Wedra Aprison (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
We sought to investigate how families in Jorong Balai Panjang Nagari Saniang Baka, X Koto Singkarak District, Solok Regency, teach moral principles to their children. The author is interested in studying the role of parents in developing morals in children in the family environment at Jorong Balai Panjang Nagari Saniang Baka because they want to know about the younger generation who reflect superior ethics (morals). This research highlights several aspects of the depth of information collected from interviews and uses qualitative methods supported by field observation techniques. In District The leader or head of the jorong and friends act as informants to support the research. According to research, parents have a significant influence on the development of their children's moral principles (morals). This research highlights the important role of parents in shaping children's moral character in the family context. Parents play a number of roles, including modeling appropriate language and accent when speaking to their children, influencing their behavior and relationships, being role models and motivators, and teaching their children about religion. If these roles are fulfilled, it is likely that the offspring will have good morals. There are many things that are difficult for parents to regulate regarding children's behavior, such as contact with people outside the household, cell phone use, and the games they play. All of these obstacles lie within the child himself. If the child is willing to change and is willing to listen to the words of advice from his parents then these obstacles can be overcome.